PENGARUH KUALITAS PRODUK, PROMOSI ONLINE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN LIVINT THRIF DI SITUBONDO DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Sindi Dayu Maisyaroh; Riska Ayu Pramesthi; Yudha Praja (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of product quality, online promotions, and service quality on purchasing decisions at Livint Thrift in Situbondo, with purchase intention as an intervening variable. The growing thrift business and intense competition have encouraged businesses to implement effective marketing strategies. This study employed a quantitative approach with a survey method, distributing questionnaires to 99 respondents, who were Livint Thrift consumers. Data analysis used Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.0 software. The results showed that product quality, online promotions, and service quality had a positive and significant effect on purchase intention and purchase decisions. Furthermore, purchase intention proved to be an intervening variable, strengthening the influence of the three independent variables on purchase decisions. These findings are expected to provide input for Livint Thrift in formulating more effective marketing strategies to increase its business competitiveness.